2014
DOI: 10.1158/0008-5472.can-13-1896
|View full text |Cite|
|
Sign up to set email alerts
|

UTX and MLL4 Coordinately Regulate Transcriptional Programs for Cell Proliferation and Invasiveness in Breast Cancer Cells

Abstract: Histone methyltransferases and demethylases reversibly modulate histone lysine methylation, which is considered a key epigenetic mark associated with gene regulation. Recently, aberrant regulation of gene expression by histone methylation modifiers has emerged as an important mechanism for tumorigenesis. However, it remains largely unknown how histone methyltransferases and demethylases co-regulate transcriptional profiles for cancer cell characteristics. Here, we show that in breast cancer cells, the histone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
181
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(195 citation statements)
references
References 49 publications
11
181
2
1
Order By: Relevance
“…H3K4me3 is enriched at the TSS of transcriptionally active genes (16)(17)(18)(19), although whether this modification is a passive mark for active transcription or plays an active role in promoting transcription is currently under debate. Nevertheless, our group and others have observed both global and local changes in H3K4me3 at promoters of genes with cancer-promoting activity, in cancer cells (14,25,26,53,54). Methylation of H3K4 is primarily catalyzed by TrxG members, with the modification of H3K4me3 chiefly catalyzed by hSETD1A (26,27,(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…H3K4me3 is enriched at the TSS of transcriptionally active genes (16)(17)(18)(19), although whether this modification is a passive mark for active transcription or plays an active role in promoting transcription is currently under debate. Nevertheless, our group and others have observed both global and local changes in H3K4me3 at promoters of genes with cancer-promoting activity, in cancer cells (14,25,26,53,54). Methylation of H3K4 is primarily catalyzed by TrxG members, with the modification of H3K4me3 chiefly catalyzed by hSETD1A (26,27,(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 80%
“…5B). While we are unsure how global levels of H3K4me3 are maintained following hSETD1A knockdown in breast cancer, the contribution of other TrxG family member(s), such as hSETD1B and MLL1-5, to the maintenance of H3K4me3 in breast cancer cells could be significant (14,27,64). In support of this possibility, we observed a significant increase in the transcript levels of hSETD1B in primary and metastatic breast cancer samples ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Thieme et al (58) showed that Kdm6a positively regulates the migration of hematopoietic stem cells. In addition, Kim et al (60) reported that knockdown of KDM6A decreased the migration and invasion capacity of breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%